2011
DOI: 10.1155/2011/750468
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cordycepin on Steroidogenesis and Apoptosis in MA‐10Mouse Leydig Tumor Cells

Abstract: Cordycepin is a natural pure compound extracted from Cordyceps sinensis (CS). We have demonstrated that CS stimulates steroidogenesis in primary mouse Leydig cell and activates apoptosis in MA-10 mouse Leydig tumor cells. It is highly possible that cordycepin is the main component in CS modulating Leydig cell functions. Thus, our aim was to investigate the steroidogenic and apoptotic effects with potential mechanism of cordycepin on MA-10 mouse Leydig tumor cells. Results showed that cordycepin significantly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 73 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…A major outstanding issue that is hampering the development of cordycepin as a lead compound is the lack of a clearly identified cordycepin-binding target molecule and a mechanism of action that connects this binding with the therapeutic effects. Proposed binding targets include poly (A) polymerases, adenosine receptors, CDK2, PARP1, AKT, AMPK, FGFR2 and RuvB-like ATPase 2 (RUVBL2) [ 31 , 32 , 35 , 40 , 65 , 66 , 106 , 145 , 155 , 167 , 201 , 210 , 239 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 ]. A recent careful evaluation of AMPK as a cordycepin target concluded that although it is bound and activated by cordycepin monophosphate, AMPK activation is not responsible for the effects of cordycepin on cell survival [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major outstanding issue that is hampering the development of cordycepin as a lead compound is the lack of a clearly identified cordycepin-binding target molecule and a mechanism of action that connects this binding with the therapeutic effects. Proposed binding targets include poly (A) polymerases, adenosine receptors, CDK2, PARP1, AKT, AMPK, FGFR2 and RuvB-like ATPase 2 (RUVBL2) [ 31 , 32 , 35 , 40 , 65 , 66 , 106 , 145 , 155 , 167 , 201 , 210 , 239 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 ]. A recent careful evaluation of AMPK as a cordycepin target concluded that although it is bound and activated by cordycepin monophosphate, AMPK activation is not responsible for the effects of cordycepin on cell survival [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al considered that cordycepin is a potent anti-inflammatory and analgesic medicine. There are several studies demonstrating that C. sinensis stimulates steroidogenesis in primary mouse Leydig cell and activates apoptosis in MA-10 mouse Leydig tumor cells in dose- and time-dependent manners [ 27 , 28 ]. The steroidogenic and apoptotic mechanism of cordycepin is also clear—cordycepin stimulated intracellular PLC/PKC and MAPK signal transduction pathways to induce steroidogenesis and cell death in MA-10 mouse Leydig tumor cells [ 29 ].…”
Section: Chemical Constituents and Their Corresponding Pharmacologmentioning
confidence: 99%
“…Afterward, the cAMP formation was inhibited, then the serine/threonine kinase glycogen synthase kinase (GSK)-3β/β-catenin signaling pathway and subsequently cell division were indirectly inactivated and suppressed, respectively ( 15 ). Additionally, it has been also documented that cordycepin effects on inhibiting platelet aggregation, inducing steroid formation, and with broad-spectrum antibiotic activity by inhibiting NAD + -dependent DNA ligase ( 13 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%